Dental caries and the nutritional status of preschool children - a spatial analysis - Juliana Alvares Duarte Bonini Campos (Ciência & Saúde Coletiva, 2011)
OBJECTIVE: This cross-sectional study sought to conduct a spatially analysis of the distribution of dental caries and the nutritional status (NS) of 5-year-old preschool children of public schools in the city of Araraquara, São Paulo, Brazil. METHODS: The sample was selected in a stratified probabilistic manner. A dental examination was conducted to investigate the dmft index. The anthropometric indicators of the weight/height (W/H), height/age (H/A), weight/age (W/A) and body mass index (BMI) were calculated to estimate the NS. A descriptive statistical analysis was conducted and a thematic map was created. At the end of the study 491 children had full address codification. A GPS device was used to ascertain the geographic reference points. A pluri-directional semi-variogram was elaborated. RESULTS: It was revealed that both variables presented a pure nugget effect showing the absence of a spatial correlation, in other words the dmft and nutritional status are not regionalized variables, and their values do not reveal direct spatial dependence. CONCLUSIONS: Dental caries and nutritional status are health conditions that do not reveal spatial dependence. Ultimately, the combination of these indicators with others can produce spatial dependence effects.